Assessing timber extraction by using the RIMBAKA R2020- a timber harvester on a steep terrain in Ulu Jelai Forest Reserve, Peninsular Malaysia - Kamarudin, Norizah; Ismail, Mohd Hasmadi; Jusoff, Kamaruzaman; Mohd Sood, Alias; Acuna, Mauricio (Universiti Putra Malaysia Press, 2013)
In this study, the extraction operation of a RIMBAKA Timber Harvester R2020-A on steep terrain was investigated. A continuous time study was carried out to estimate the operational efficiency of the RIMBAKA timber harvester. Four dependent variables were observed to investigate their impacts on the extraction phases: skidding distance, hauling distance, volume and slope. A total of 48 working cycles were time studied. During the operation, RIMBAKA extracted 3.55 m3 of logs per cycle and had a machine utilization rate of 78%, with a corresponding productivity of 45.92 m3/PMH15. The unit cost of RIMBAKA was RM 4.64/m3. Meanwhile, hauling distance and log volume had a major effect on the productivity of the harvester during the extraction phase. Thus, a better understanding of the integrated effect on the productivity of the RIMBAKA extraction operation, in combination with the rest of machines of the harvesting system, will better help predicting the efficiency and productivity of the whole system.